La gestión de la ayuda y las políticas públicas para el desarrollo. Estudio del caso de Cabo Verde - Boza-Chirino, J.; González-Hernández, M.; De-León-Ledesma, J. (Revista Iberoamericana de Estudios de Desarrollo)
This work contributes to clarifying the complex relations between aid, governance and development, based on the Cape Verde experience. Complementing evidence on correlations between aid, growth and development, a survey carried out with experts and the results derived from the estimation of a confirmatory factorial analysis model note that among the key factors in the success of Cape Verde is that the process for managing the aid has been integrated into the governance of the country. This has allowed strategic national leadership (appropriation), clear criteria for donors (alignment with strategic national lines), coordination of all donor intervention (harmonisation), improvement in design and execution of indicator-based policies (performance-oriented indicators) and the introduction of transparent habits and accountability in all significant related areas.